Why Malaysian second board companies switch auditors: Evidence of Bursa Malaysia - Ismail, S.; Joher, Huson; Nassir, A.; Ali, M. (Euro Journals Publishing, Inc. 2008, 2008)
The auditor switching phenomenon was found to have implications to the value credibility of financial reporting and the cost of monitoring management activities Therefore, it has been widely and extensively studied in developed countries by academicians, accounting professionals and industry experts due to the great number of switches in the early 1970 s. Despite the growing concerns of this issue, few studies appear to have been made in Malaysia to examine the significant reasons of auditor switching. Thus, this study was conducted with the objective of identifying major determinants of auditor switch among companies listed on Second Board of Bursa Malaysia, formerly known as Kuala Lumpur Stock Exchange (KLSE), especially during the period from 1997 to 1999, which coincide with the Asian financial crisis. In order to examine the determinants of auditor switch among second board companies, this study uses logistic regression model, in particular, the stepwise method. From the results, this study indicates that leverage, growth turnover, financing activities, longevity of audit engagement and audit fee were the significant determinants of auditor switch during the period of financial International Research Journal of Finance and Economics -Issue 13 (2008) 124 crisis. However, receiving qualified audit report was not found to be the factor of auditor switch among the Second Board companies in Malaysia during this period.